Towards the assessment of linguistic vitality. A proposal (Atti del Sodalizio Glottologico Milanese, 2014)
The paper deals with the establishment of a series of procedures to find out and measure the subjective ethnolinguistic vitalities of lesser used languages when the overall sociolinguistic situation is quite well-known. Such a goal can be achieved through the analysis of a number of sociolinguistic and pragmatic parameters – discussed in depth – and a proper mathematical treatment of the emerging data. Examples are given, taken from research experiences throughout Europe. KEYWORDS: sociolinguistics, linguistic vitality, quantitative research, minorities, repertoires